An Anchor-Free Localization Scheme with Kalman Filtering in ZigBee Sensor Network. (28th February 2013) - Isokawa, Teijiro; Motomura, Shun; Ohtsuka, Junya; Kawa, Hironobu; Nakashima, Satoshi; Kamiura, Naotake; Matsui, Nobuyuki
Abstract : A localization scheme for wireless sensor networks is proposed and its performances are investigated in this paper. The proposed scheme is an anchor-free scheme, in which no geometrical information of sensor nodes is required for their localization. Thus, only local interaction among sensor nodes is used to estimate their locations. This scheme employs the link quality indicator and hop count between sensor nodes for location estimation. A weighted averaging and Kalman filtering schemes are incorporated in order to reduce the effects of the measurement errors in the obtained values of the link quality indicator. We performed experiments by implementing the proposed scheme on ZigBee sensor modules. The results of our experiments indicate that estimation could be successfully performed for networks comprising four sensor nodes.